1992
DOI: 10.1128/jvi.66.9.5363-5372.1992
|View full text |Cite
|
Sign up to set email alerts
|

Identification and transcriptional analyses of the UL3 and UL4 genes of equine herpesvirus 1, homologs of the ICP27 and glycoprotein K genes of herpes simplex virus

Abstract: The DNA sequence of 3,240 nucleotides of the XbaI G fragment located in the unique long (UL) region of the equine herpesvirus 1 genome revealed two major open reading frames (ORFs) designated UL3 and UL4. The UL3 ORF of 470 amino acids (aa) maps at nucleotides (nt) 4450 to 3038 from the long terminus, and its predicted 51.4-kDa protein product exhibits significant homology to the ICP27 alpha regulatory protein of herpes simplex virus type 1 (HSV-1; 32% identity) and to the ORF4 protein of varicella-zoster viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 60 publications
0
30
0
Order By: Relevance
“…The IR4 protein is ex- pressed abundantly and localizes predominantly to the nucleus (26,27), and transient expression assays demonstrate that the IR4 protein can activate a variety of EHV-1 early and late promoters in the presence of other EHV-1 trans-activators, such as the immediate-early protein and the UL3 protein (28). The UL3 protein exhibits significant homology to the ICP27 immediate-early regulatory protein of HSV-1 (32% identity) and to the ORF4 protein of varicella-zoster virus (13% identity) (66). Studies with ICP27 temperature-sensitive and deletion mutants have demonstrated that HSV-1 ICP27 possesses the ability to down-regulate the immediate-early gene and some early genes and to up-regulate late gene expression (44-46, 56, 57, 60).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IR4 protein is ex- pressed abundantly and localizes predominantly to the nucleus (26,27), and transient expression assays demonstrate that the IR4 protein can activate a variety of EHV-1 early and late promoters in the presence of other EHV-1 trans-activators, such as the immediate-early protein and the UL3 protein (28). The UL3 protein exhibits significant homology to the ICP27 immediate-early regulatory protein of HSV-1 (32% identity) and to the ORF4 protein of varicella-zoster virus (13% identity) (66). Studies with ICP27 temperature-sensitive and deletion mutants have demonstrated that HSV-1 ICP27 possesses the ability to down-regulate the immediate-early gene and some early genes and to up-regulate late gene expression (44-46, 56, 57, 60).…”
Section: Discussionmentioning
confidence: 99%
“…The 8-nucleotide (nt) recombination site was confirmed on a pDI2227 subclone. This ORF (designated as IR4/UL3 for the hybrid of IR4 and UL3) appears to have the transcription initiation site of the IR4 gene, which gives rise to an early mRNA and a late mRNA, as described by Holden et al (27), and the polyadenylation signal of the UL3 gene, as described by Zhao et al (66). A comparison of the IR4 sequences in the hybrid ORF with those in the IR4 gene revealed a 28-bp deletion in the upstream noncoding region, in which 4 of the 17 seven-mer repeats were missing in pDI2227.…”
Section: Sequence Analyses Of the Ir4/ul3 Hybrid Orf Of The Genome Ofmentioning
confidence: 94%
See 1 more Smart Citation
“…Mature glycoprotein K (gK) of PrV is a hydrophobic protein of 36 kDa which is present in virions and contains both highmannose as well as complex forms of N-linked glycans (25). The protein is conserved among the alphaherpesviruses, and homologous proteins or open reading frames (ORFs) have also been described for herpes simplex virus types 1 and 2 (HSV-1 and -2), bovine herpesvirus 1, equine herpesvirus 1, varicella-zoster virus (VZV), infectious laryngotracheitis virus, and Marek's disease virus (12,17,20,32,34,35,39). All deduced gK homologous proteins are characterized by the presence of four hydrophobic domains of sufficient length to be membrane spanning.…”
mentioning
confidence: 99%
“…During a productive lytic infection, the genes of EHV-1 are coordinately expressed and temporally regulated in immediate-early (IE), early (E), and late (L) fashions (15,16). EHV-1 EICP22 (previously named IR4; ICP22 homolog) (23), EICP27 (previously named UL3; ICP27 homolog) (63), and ICP0 (3) are regulated as E genes, in contrast to the case for herpes simplex virus type 1 (HSV-1), in which they are members of the IE gene family (2,26,27,31,40,58).…”
mentioning
confidence: 99%